2012
DOI: 10.1038/ejhg.2012.222
|View full text |Cite
|
Sign up to set email alerts
|

Severe SMA mice show organ impairment that cannot be rescued by therapy with the HDACi JNJ-26481585

Abstract: Spinal muscular atrophy (SMA) is the leading genetic cause of early childhood death worldwide and no therapy is available today. Many drugs, especially histone deacetylase inhibitors (HDACi), increase SMN levels. As all HDACi tested so far only mildly ameliorate the SMA phenotype or are unsuitable for use in humans, there is still need to identify more potent drugs. Here, we assessed the therapeutic power of the pan-HDACi JNJ-26481585 for SMA, which is currently used in various clinical cancer trials. When adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 69 publications
2
48
0
Order By: Relevance
“…Examination of quercetin-treated mice postmortem revealed the presence of widespread gross organ defects previously reported in SMA mice (Figure 7J), where systemic pathology is known to target organs including the heart and liver (10,14,16). In order to examine the possible causes of this failure to ameliorate nonneuromuscular, systemic pathology (even when quercetin was administered systemically via i.p.…”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…Examination of quercetin-treated mice postmortem revealed the presence of widespread gross organ defects previously reported in SMA mice (Figure 7J), where systemic pathology is known to target organs including the heart and liver (10,14,16). In order to examine the possible causes of this failure to ameliorate nonneuromuscular, systemic pathology (even when quercetin was administered systemically via i.p.…”
Section: Figurementioning
confidence: 88%
“…However, recent studies have revealed that SMA, particularly in its most severe forms, is a multisystem disorder (10), with other regions of the nervous system also being affected (e.g., the hippocampus; ref. 11) as well as nonneuronal tissues and organs, including heart (12), vasculature (13), liver (14), pancreas (15), lung, and intestines (16). This suggests that SMN deficiency causes perturbations across a wide range of cells and tissues in SMA, albeit with motor neurons being the most vulnerable cell type.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular defects are the most obvious hallmarks of SMA, but SMN is ubiquitously expressed and numerous studies have suggested nonneuronal requirements for SMN function in heart (57-59), liver (60), muscle vascular system (61), lung, intestine (62), and pancreatic islets (63). Therefore, it was not surprising that endosomal defects were observed in other C. elegans tissues when SMN levels were compromised.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that SMA is a complex and multisystemic disorder, although it is phenotypically expressed mainly as a neuromuscular disease [13,61,106,107]. It appears that muscle and nerve may be independently affected by SMN deficiency [17,107], and muscle has only a minor impact on SMA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%